Faktor Penyebab dalam Pencegahan Obesitas pada Balita di Kelurahan Bincar Kecamatan Padangsidimpuan Utara - Nasution, Nurul Hidayah; Pebrianthy, Lola (Universitas Aufa Royhan, 2019)
Obesity is a pathological state with the accumulation of excess fat from normal bodily functions (Soetjiningsih, 2012). Obesity is one of the problems faced by Indonesia in addition to malnutrition. Inequality of income that accompanies Indonesia's economic growth can exacerbate the problems facing Indonesia. This research aims to determine the causal factors in the prevention of obesity in children under five in Bincar Village, Padangsidimpuan District. Type of research was analitic, cross sectional study design. The independent variable is the respondent's characteristics (age, education, source of information and occupation), knowledge and eating patterns. The dependent variable is prevention of obesity. The results showed, there is no relationship between parental age, parental education, sources of information, parental occupation, parental knowledge and children's diet with the prevention of obesity in infants. The causative factor in the prevention of obesity in infants is influenced by education, information sources and knowledge together being the most dominant variable related to obesity prevention, OR value = 2.52. Efforts can be made such as the use of print and electronic media by parents as a source of information in order to increase parental knowledge in preventing obesity in infants. Outreach to parents about healthy food and healthy snacks that are appropriate and the importance of supervision of food consumed by children under five.